The power of knowledge how information and technology made the modern world - Black, Jeremy 1955- (Yale University Press, 2015)
"Information is power. For more than five hundred years the success or failure of nations has been determined by a country's ability to acquire knowledge and technical skill and transform them into strength and prosperity. Leading historian Jeremy Black approaches global history from a distinctive perspective, focusing on the relationship between information and society and demonstrating how the understanding and use of information have been the primary factors in the development and character of the modern age. Black suggests that the West's ascension was a direct result of its institutions and social practices for acquiring, employing, and retaining information and the technology that was ultimately produced. His cogent and well-reasoned analysis looks at cartography and the hardware of communication, armaments and sea power, mercantilism and imperialism, science and astronomy, as well as bureaucracy and the management of information, linking the history of technology with the history of global power while providing important indicators for the future of our world"--Provided by publisher.